The mutual benchmarking method for SMEs' competitive strategy development - Katarzyna Rostek (Foundations of Management, 2013)
Competitive advantage is a relative feature, evaluated in respect of other competing enterprises. The gaining of sustainable competitive advantage is conditioned by knowledge of own performance and the results of the competitive environment. SMEs have limited opportunities to obtain such information on their own. The method of mutual benchmarking changes this situation by introducing the collaborative network. The aim of the cooperation is to support each of the group members to achieve sustainable competitive advantage, which is the result of a conscious strategy, and not only a matter of chance. This cooperation is based on the collecting and processing of data and sharing information through a common IT platform: for example, a group of Polish SMEs was shown how to implement such a common IT solution and how to provide the information preparing within the proposed service. The whole is a complete proposal for effective support of creating a competitive strategy in SMEs.
Keywords: 650; competitiveness; competitive position; competitive analysis; competitive strategy; mutual benchmarking; SME sector